2011
DOI: 10.3791/2809
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Analysis of Mouse Erythroid Progenitors using the CD71/TER119 Flow-cytometric Assay

Abstract: The study of erythropoiesis aims to understand how red cells are formed from earlier hematopoietic and erythroid progenitors. Specifically, the rate of red cell formation is regulated by the hormone erythropoietin (Epo), whose synthesis is triggered by tissue hypoxia. A threat to adequate tissue oxygenation results in a rapid increase in Epo, driving an increase in erythropoietic rate, a process known as the erythropoietic stress response. The resulting increase in the number of circulating red cells improves … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
98
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(104 citation statements)
references
References 12 publications
6
98
0
Order By: Relevance
“…A total of 20,000 events were collected and analyzed using FlowJo software version 7.6.5. Erythroid lineage was assessed using Ter119 APC/CD71 PE markers combined with the forward scatter properties (26). Hematopoietic stem/progenitor cells were differentiated using SLAM markers (CD150 PE/CD48 APC), Sca-1 FITC (Ly6A-E), c-Kit Percp Cy5.5 (CD117), CD90 PE (Thy-1), and APC-tagged lineage mixture comprising of antibodies against CD3, B220 (CD45R), Ly6G and Ly6C (Gr-1), CD11b (Mac-1), and TER119.…”
Section: Animals-heterozygousmentioning
confidence: 99%
“…A total of 20,000 events were collected and analyzed using FlowJo software version 7.6.5. Erythroid lineage was assessed using Ter119 APC/CD71 PE markers combined with the forward scatter properties (26). Hematopoietic stem/progenitor cells were differentiated using SLAM markers (CD150 PE/CD48 APC), Sca-1 FITC (Ly6A-E), c-Kit Percp Cy5.5 (CD117), CD90 PE (Thy-1), and APC-tagged lineage mixture comprising of antibodies against CD3, B220 (CD45R), Ly6G and Ly6C (Gr-1), CD11b (Mac-1), and TER119.…”
Section: Animals-heterozygousmentioning
confidence: 99%
“…71 The different stages of differentiation post CFUe were identified as proerythroblasts, basophilic, polychromatic, orthochromatic erythroblasts, reticulocytes and red blood cells. [71][72][73] Upon the binding of erythropoietin to EPO receptor (EPOR), the tyrosine kinase/Janus kinase 2 (JAK2) is phosphorylated, which in turn activates multiple signal transduction pathways crucial in erythropoiesis ( Figure 3). One such pathway consists of activation of Signal Transducer and Activator of Transcription 5 (Stat5) and downstream antiapoptotic B-cell lymphoma-extra large (BclxL) protein.…”
mentioning
confidence: 99%
“…To know the existent of erythropoiesis we examined the expression of TER-119 antigen as a specific marker of erythroid-lineage [15][16][17]. In this experiment we showed that the number of TER-119 + cells in the bone marrow of CD122 -/-decreased before the manipulation with regulatory T cells.…”
Section: Cd4mentioning
confidence: 74%